Odpowiedzi

2010-02-10T14:06:22+01:00
X - 4,8 = 1½
4,8 + 1,5 = 6,3
x=6,3

6 ⅓ - z = 2,25
6,(3) - 2,25= 4,5
z=4,5
1 5 1
2010-02-10T14:10:37+01:00
X-4,8=1,5
x=1,5+4,8
x=6,3


6 ⅓ -z=2,25
-z=2,25 - 6⅓
z=-¼


⅓ *w=6,4
w=6,4 /⅓
w=19,2


k/ 6¼=1,5
k=1,5*6¼
k=2,25

9,36/c=3⅗
c=3⅗*9,36
c=16,848
1 5 1
Najlepsza Odpowiedź!
2010-02-10T14:20:10+01:00
X - 4,8 = 1½
x = 1½ +4,8
x = 1,5 + 4,8
x = 6,3

6 ⅓ - z = 2,25
-z = 2,25 - 6⅓
-z = 2¼-6⅓
-z = 2³/₁₂ - 6⁴/₁₂
-z = -4¹/₁₂ / (-1)
z = 4¹/₁₂

⅓ * w = 6,4
⅓w = 6,4 / *3
w= 6,4*3
w = 19,2

k : 6¼=1,5
k:²⁵/₄ = 1,5
k*⁴/₂₅ = 1,5 / *(²⁵/₄)
k = ³/₂ * ²⁵/₄
k = ⁷⁵/₈
k = 9 ³/₈

9,36 : c = 3⅗ / *c
9,36 = 3⅗ c
¹⁸/₅ c = 9,36 / *⁵/₁₈
c = ²³⁴/₂₃ * ⁵/₁₈
c = ⁶⁵/₂₃
c= 2¹⁹/₂₃
1 5 1